Chitooligosaccharides as Antibacterial, Antibiofilm, Antihemolytic and Anti-Virulence Agent against Staphylococcus aureus - Khan, Fazlurrahman; Lee, Jang-Won; Pham, Dung T.N.; Kim, Young-Mog (Current Pharmaceutical Biotechnology, 2019)
Background: Staphylococcus aureus nosocomial infections with a high mortality rate in human and animals have been reported to associate with bacterial biofilm formation, along with the secretion of numerous virulence factors. Therefore, the inhibition of biofilm formation and attenuation of virulence determinants are considered as a promising solution to combat the spread of S. aureus infections. Modern trends in antibiofilm therapies have opted for the active agents that are biocompatible, biodegradable, non-toxic and cost-effective. Owning the aforementioned properties, chitosan, a natural N-acetylated carbohydrate biopolymer derived from chitin, has been favorably employed. Recently, the chitosan structure has been chemically modified into Chitooligosaccharides (COS) to overcome its limited solubility in water, thus widening chitosan applications in modern antibiofilm research. In the present study, we have investigated the antibacterial, antibiofilm and anti-virulence activities against S. aureus of COS of different molecular weights dissolved in neutral water. Methods: The study of bactericidal activity was performed using the micro-dilution method while the biofilm inhibition assay was performed using crystal-violet staining method and confirmed by scanning electron microscopic analysis. The inhibition of amyloid protein production was confirmed by Congo Red staining. Results: Results showed that low molecular weight COS exhibited bactericidal activity and reduced the bacterial amylogenesis, hemolytic activity as well as H2O2 resistance properties, while slightly inhibiting biofilm formation. The present study provides a new insight for further applications of the water-soluble COS as a safe and cost-effective drug for the treatment of S. aureus biofilm-associated infections. Conclusion: Reducing the molecular weight of chitosan in the form of COS has become an effective strategy to maintain chitosan biological activity while improving its water solubility. The low molecular weight COS investigated in this study have effectively performed antibacterial, antibiofilm and antivirulence properties against S. aureus.
Keywords: e-DNA